Portrait of the Value of Islamic Education in the Novel "Kasidah Lereng Bukit" (Semantic Study by Achmad Munif) - Khotimah, Khusnul (MANAGIERE: Journal of Islamic Educational Management, 2023)
Educational messages are statements contained and sourced from the Qur'an and as-Sunnah or other sources which are interpretations of these two sources in the form of Islamic teachings. In the context of this study, the educational messages referred to are statements contained in the novel "Kasidah Lereng Bukit" by Achmad Munif, which contains Islamic teachings originating from the Qur'an and as-Sunnah, with the theme of faith, Islamic law and good morals. aims amar ma'ruf nahi munkar. One of the limitations of literature is everything that is written. Its relationship with education can be used as a medium of da'wah in writing. Literature aside from being a tool for spreading ideology, literature is also considered capable of providing life experiences and noble human values for its readers. The existence of a novel cannot be separated from the author's background regarding education, knowledge, personal experience, religion and others so that the literary work he produces has its own characteris- tics. Achmad Munif was able to greet readers intimately through his writings, in his work the writer was able to play with emotions, attracting readers through the characters in the story. This study focuses on what is the message of Islamic education contained in the novel "Kasidah Lereng Bukit" by Achmad Munif. How is the educational message conveyed through the integration of the intrinsic elements of the fictional story of the novel "Kasidah Lereng Bukit" by Achmad Munif. The research method used is the study of literature analysis, according to Hawkes in the analysis of literary works the elements of its formation are de- scribed. Thus, the overall meaning will be understood. This is because a literary work is a complete work. Thus, this study will give birth to the first. The forms of Islamic education messages contained in the novel "Kasidah Lereng Bukit" by Achmad Munif are often insepa- rable from three aspects, namely: Aqidah aspects by prohibiting belief in shamans, Shari'ah aspects by practicing obligatory worship, and the moral aspect, namely endeavor (effort) and prayer are two ways that cannot be separated to get what one wants, stay away from bad prej- udice, be grateful for the favors that have been bestowed, repent and regret the sins that have been committed. Second, judging from the intrinsic elements of the novel "Kasidah Lereng Bukit" most of the plot is straight, the characters are all Muslims. In terms o f tension, it is a primidal plot, namely the climax is not at the beginning and at the end but in the middle, while in terms of the storytelling sequence using a progressive plot, the story opens from the beginning of the story and closes at the end of the story.